2008
DOI: 10.1159/000119522
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms, Vascular Risk Factors and Mild Cognitive Impairment

Abstract: Aims: We evaluated the impact of depressive symptoms on the rate of incident mild cognitive impairment (MCI) after a 3.5-year follow-up, and we assessed the interaction between depressive symptoms and vascular risk factors for incident MCI. Methods: A total of 2,963 individuals from a sample of 5,632 65- to 84-year-old subjects were cognitively and functionally evaluated at the 1st and 2nd surveys of the Italian Longitudinal Study on Aging, a prospective cohort study with a 3.5-year follow-up. MCI and dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 101 publications
0
29
1
6
Order By: Relevance
“…The incidence of MCI in subjects who were aged 75 years or older was approximately 6 times higher than that in subjects who were aged between 65 and 74 years. As shown in figure 2, the increase in the incidence of MCI was demonstrated to be age dependent in several previous studies [24,25,26,27,28,29,30], and the incidence doubled in the oldest members of the elderly population compared with the younger members of the elderly population in most studies [24,25,26,27,28,29]. Although each study used the same diagnostic criteria, the operation definition, sample size, length of follow-up, and assessment procedure were different, and the estimated incidence of MCI varied greatly between the studies.…”
Section: Discussionmentioning
confidence: 69%
“…The incidence of MCI in subjects who were aged 75 years or older was approximately 6 times higher than that in subjects who were aged between 65 and 74 years. As shown in figure 2, the increase in the incidence of MCI was demonstrated to be age dependent in several previous studies [24,25,26,27,28,29,30], and the incidence doubled in the oldest members of the elderly population compared with the younger members of the elderly population in most studies [24,25,26,27,28,29]. Although each study used the same diagnostic criteria, the operation definition, sample size, length of follow-up, and assessment procedure were different, and the estimated incidence of MCI varied greatly between the studies.…”
Section: Discussionmentioning
confidence: 69%
“…In fact, among the 2,963 participants, we estimated in MCI patients a depressive symptoms prevalence rate of 63.3%, and during the 3.5-year follow-up, an incidence rate of 29.6 per 100 person-years of depressive symptoms (Solfrizzi et al, 2007). Furthermore, we did not observe any significant association between depressive symptoms and incident MCI, and no socio-demographic variables or vascular risk factors modified the association between depressive symptoms and incident MCI (Panza et al, 2008).…”
Section: Introductionmentioning
confidence: 55%
“…The diagnosis was based on the criteria for dementia syndrome of the Diagnostic and Statistical Manual of Mental Disorders, 3rd edition revised (American Psychiatric Association, 1987), the criteria for possible and probable AD of the National Institute of Neurological and Communicative Disorders and Stroke and the Alzheimer's Disease and Related Disorders Association (McKhann et al, 1984), and the criteria for vascular dementia and other dementing diseases of the International statistical Classification of Diseases and related health problems, 10th revision (World Health Organization, 1992). We generally adhered to the diagnostic criteria for MCI as defined by Petersen and colleagues (Petersen et al, 1999) with some modifications (Solfrizzi et al, 2004(Solfrizzi et al, , 2006Panza et al, 2008;Solfrizzi et al, 2007) and we did not require subjective memory complaints (SMC), allowing also for the presence of noncognitive disabilities and comorbid illnesses. We retroactively applied these criteria to the data collected in this study between 1992-1995: (1) no dementia; (2) normal general cognitive functioning as assessed by MMSE using age and education based norms (this cutoff was calculated by subtracting 1.5 SD from the mean ageand education-adjusted MMSE scores after excluding subjects with prevalent dementia).…”
Section: Classification Of Dementia and MCImentioning
confidence: 99%
“…For instance, a study by Steenland et al [52] found that depression, based on clinical judgment, significantly predicted incident MCI in 5,607 individuals with a mean age of 73 years. However, some studies did not find such associations [12,60,61,62,63]. …”
Section: Discussionmentioning
confidence: 99%